2015
DOI: 10.1007/978-94-017-9573-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Findings: The Time Is not yet Ripe for a Policy for Biobanks

Abstract: Incidental findings (IFs) are acknowledged to be among the most important ethical issues to consider in biobank research. Genome-wide association studies and disease-specific genetic research might reveal information about individual participants that are not related to the research purpose, but may be relevant to those participants' future health. In this article, we provide a synopsis of arguments for and against the disclosure of IFs in biobank research. We argue that arguments that do not distinguish betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Accordingly, it has recently been argued that the time is not yet ripe for issuing recommendations. 70 …”
Section: Return Of Incidental Findingsmentioning
confidence: 99%
“…Accordingly, it has recently been argued that the time is not yet ripe for issuing recommendations. 70 …”
Section: Return Of Incidental Findingsmentioning
confidence: 99%
“…2 However, it has been suggested that participants should be offered individual genetic information, such as incidental findings (IFs). 3 The main arguments for disclosure of IFs, presented in a synopsis of the argumentative field 4 are that it can benefit participants' health, promote participants' autonomy and support reciprocity between participants and research groups. In addition, research can benefit from offering genetic information to participants, because it can increase participation when people find that they can have personal gain from participating, 5 and recontacting participants if something of great importance is discovered can maintain the general public's trust in research.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no overall consensus on when to tell and when not to tell 4 participants of incidental findings (Viberg et al, 2014). Careful planning of procedures to satisfy local 5 or national expectations are therefore necessary to ensure that donor interests are managed 6…”
mentioning
confidence: 99%